The Effects of Environmental Determinants and Vector Control Methods on Aedes aegypti Larval Presence at Bakauheni Seaport and Radin Inten II Airport - Ershad Hari Indrajid; Dyah Wulan SRW; Sri Aryanti; Endah Setyaningrum; Sutarto Sutarto; Samsul Bakri (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2026)
Seaports and airports are strategic points characterized by high mobility of people and goods, making them potential hubs for the dissemination of dengue vectors. The presence of Aedes aegypti larvae is strongly influenced by environmental factors and the effectiveness of vector control methods. This study employed an analytic observational quantitative design with a cross-sectional approach. The study was conducted at Bakauheni Seaport and Radin Inten II Airport in 2025. All identified at-risk sites were included as the study sample. The independent variables were temperature, humidity, physical control, and chemical control, whereas the dependent variable was the presence of Aedes aegypti larvae. Data were analyzed using multivariate logistic regression. The findings revealed that humidity and chemical control were the primary determinants of Aedes aegypti larval presence at Bakauheni Seaport. In contrast, at Radin Inten II Airport, physical control played a more prominent role than the other factors examined. Therefore, strengthening physical vector control integrated with chemical control is recommended as the principal strategy for dengue prevention at points of entry.